Sequences Analysis of a Gene Encoding Extracellular Xylanase in Streptomyces costaricanus 45I-3 - S. Sipriyadi; Aris Tri Wahyudi; Maggy Thenawidjaja Suhartono; Anja Meryandini (Universitas Gadjah Mada, 2015)
Streptomyces costaricanus 45I-3 is a bacterial strain belongs to actinomycetes group isolated from peat soil. Thebacterium is known to produce extracellular xylanase. The aims of this study were to analyze DNA sequence andsub-clone gene involved in the synthesis of extracellular xylanase. Complete DNA sequence predicted to encodexylanase genes was isolated from bacterial genome using Inverse Polymerase Chain Reaction (I-PCR). Total DNAsequence of 1664 bp in size obtained from I-PCR consisted of two open reading frames (ORF) in opposite direction.ORF1 was 1029 bp and ORF2 (partial sequence) was 309 bp. Analysis sequence using BlastX indicated that ORF1was homologous with xylanase bacterium enrichment culture clone Xyl8B8 (GenBank accession No. AFH35005.1),i.e. 95% in identity and 99% in similarity. In addition, ORF2 was homologous with glyoxalase bacterium enrichmentculture clone Xyl8B8 (GenBank accession No. AFH35007.1), i.e. 95% in identity and 98% in similarity. Analysis ofamino acid sequence revealed that ORF1 consisted of 2 domains, i.e. glyco-hydrolase 11 (GH11) and CarbohydrateBinding Type 2 (CBM2). Active site was found at 130th amino acid on GH11 domain. Visualization of 3-dimensionstructure showed that 1029 bp fragment is of 19 areas.